Topographical Characteristics of Lower Barakar Basin: A Geospatial Approach - Sinha, Surbhi; Rai, Vinay Kumar (National Geographical Journal of India, 2022)
The evolution and development of a drainage network largely depends upon the surface topography of a landscape. Even topographic attributes such as overland flow, sub-surface flow, stream flow etc. are highly determined by the relief and slope aspects of the basin area. Topography influences evolution of landforms, soil development, vegetation growth, types of settlement, agricultural pattern etc. So it becomes very important to quantify different topographical parameters so that proper watershed management can be done. This work is an attempt to evaluate existing topography of study area using topographical sheets and SRTM DEM data. For calculation and analysis of data MS Excel is used while Geographical Information System (GIS) is used for mapping purpose. Present work provides better understanding of surface and relief aspects of landforms in Lower Barakar basin